Sodium sulfide-based polysulfide polymers: synthesis, cure, thermal and mechanical properties. (2nd November 2022) - Sheydaei, Milad
Abstract : In this study, a series of polysulfide polymers were synthesized using aqueous monomer (sodium sulfide) and organic monomers (methylene dichloride, ethylene dichloride, 1, 4-dichlorobutane, and α, α′-dichloro- p -xylene) via interfacial polymerization. Next, thepolymers, sulfur, zinc oxide (ZnO), stearic acid, and N -cyclohexyl-2-benzothiazole sulfenamide (CBS), were compounded using a two-roll mill and cured by a rheometer. The as-synthesized and cured samples are characterized by Fourier transform infrared (FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Shore A, and tensile tests. Also, the molecular weight of the as-synthesized samples was determined by proton nuclear magnetic resonance ( 1 H NMR). The results showed that in the as-synthesized linear polymers, with increasing the number of carbon in the structure, crystallinity, hardness, glass transition temperature ( Tg ), and melting point ( Tm ) decrease. Also, the investigation of thermal degradation showed that poly( p -xylene sulfide) and poly(butylene sulfide) have the lowest and highest thermal resistance, respectively. The results of polymerization yield showed that without the presence of tetrabutylammonium bromide (TBAB), which is used as a phase transfer catalysts (PTC), the polymerization reaction of poly(butylene sulfide) and poly( p -xylene sulfide) is inefficient. The samples have a completely amorphous structure after the curing process. Moreover, the Tg, thermal resistance, and hardness increased. GRAPHICAL ABSTRACT: UF0001